Space and the planet: taking the extra-planetary seriously in planetary thinking - J. Lossau (Geographica Helvetica)
In light of recent developments in space technology, services and commercialisation, human geographers have started to consider space exploration and extractivism as areas of critical concern. A debate that has not yet fully embraced the extra-planetary, however, is that on planetary thinking, in which scholarship has to bracket out the space environment to some extent in that it represents a mere distraction from the actually important terrestrial crises. Against such a background, the present intervention engages with the relations between the planetary and the extra-planetary, advocating explicit consideration of the latter in critical planetary thinking – notably not as a diversion from but rather as a reinforcement of the need to engage with earthly concerns. To elaborate its argument, the text first reconstructs the disregard of the extra-planetary in planetary thinking by revisiting two books that have shaped the contours of the related debate: Bruno Latour's Down to Earth and Donna Haraway's Staying with the Trouble. It then critically reflects on “Humans on Mars”, a publicly funded research initiative at Bremen University which justifies an expansionist agenda by adopting a planetary mindset, or at least planetary rhetoric. Conceptualising the extra-planetary as imagined-and-real counter-space, planetary scholars are finally being called upon to connect with off-Earth ecosystems, weaving their non-human and more-than-human components into a cosmopolitical ethics of care and responsibility. At the same time, a rupture pratique is suggested which, in turn, designates the extra-planetary as a space in which there is literally no room for humans and certainly not for the very frontier expansionist and extractivist practices that have resulted in socio-ecological crises on planet Earth.